From Prediction to Generation: A Literature Review on the Role of Generative AI in Enhancing Organizational Problem-Solving Dynamics - Eri Kusnanto; Rizal, Muhammad (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
This qualitative literature review explores the transformative role of generative artificial intelligence (GenAI) in reshaping organizational problem-solving. Moving beyond prediction, GenAI supports ideation, design, and decision-making by enhancing exploration, reducing cognitive constraints, and enabling hybrid human-machine intelligence. Drawing on recent studies in strategic management, organizational learning, and AI innovation, this review synthesizes evidence of GenAI’s capacity to augment creativity, frame redefinition, and solution diversity. The findings highlight both opportunities—such as improved search efficiency and strategic adaptability—and challenges, including algorithmic opacity, trust issues, and socio-technical complexity. Ultimately, GenAI represents a generative shift in how organizations define problems and pursue innovation, requiring thoughtful integration to maximize its cognitive and strategic value